Catalytic Influence of Oxide Component in Ni‐Based Cermet Anodes for Ammonia‐Fueled Solid Oxide Fuel Cells. Issue 2 (27th February 2015) - Yang, J.; Akagi, T.; Okanishi, T.; Muroyama, H.; Matsui, T.; Eguchi, K.
Abstract Recently, the promising prospect of ammonia as a hydrogen carrier for solid oxide fuel cells (SOFCs) has attracted significant interests. In this work, the effects of temperature, fuel content, and total flow rate of anode gas on the performance of Ni/yttria‐stabilized zirconia (Ni/YSZ) anode for ammonia‐fueled SOFCs were investigated. Based on obtained results, the utilization route of ammonia on Ni/YSZ anode was discussed; the results of electrochemical experiments were related with the catalytic decomposition bahavior of ammonia over Ni/YSZ. Moreover, the catalytic activity for ammonia decomposition and anode performance of Ni/samarium‐doped ceria (Ni/SDC) and Ni/yttrium‐doped barium cerate (Ni/BCY) were also investigated. Among these anode materials, Ni/BCY exhibited the highest ammonia decomposition activity and anode performance for ammonia‐fueled SOFCs at intermediate temperatures.